An Investigation on The Behaviour of Stock Returns in Emerging Markets - Chen, Yao (2011)
This thesis has an investigation on the behaviour of stock returns and volatility forecasting models in five Asia emerging markets—China, India, Korea, Malaysia and Indonesia so that to explore investment potential in these markets. Evidence show that returns series exhibits non-normal distribution with fat tails and the presence of volatility clustering. When comparing with developed market, emerging market obtains a higher risk-adjusted return, higher volatility, in association with relatively low correlation between these two markets. Accordingly, it is beneficial to invest in emerging markets either to earn higher returns or to diversify portfolios. However, the results also reveal a trend of increasing correlation between them, which casts doubt upon the possible diversification opportunities in emerging markets. It turns out that the benefits remain, but diminishes as emerging markets become more mature. Overviewing the outlook of the five emerging markets studied, they are still favourable destination for foreign capital flow. Furthermore, instead of simply focusing on index-based securities, more value is added by direct investments on selected emerging markets or specific stocks. As to further development in these markets, it is suggested that a path of less volatility with stable rates of returns is sustainable.